2021
DOI: 10.26434/chemrxiv.14075390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preparation of Versatile, Porous Poly-Arylthioethers by Reversible Pd-Catalysed C–S/C–S Metathesis

Abstract: Porous organic frameworks have shown a number of promising properties; however, their industrial application is usually hampered due to the lability of their linkages (imine, boroxine, etc.). Inspired by the outstanding chemical, mechanical and thermal resistance of the 1D polymer polyphenylene sulfide (PPS), we hypothesized that 2D and 3D poly-arylthioether frameworks would merge the attractive features common to porous frameworks and PPS in a single material. Herein, we report a Pd-catalysed C–S/C–S metathes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…POPs with designed functional groups have emerged as a versatile platform for many potential applications, such as catalysis, sensing, and purification. 1,3,30,31 Our new bottom-up approach allows the installation of functionality using an elaborated monomer. Hence, we prepared aldehyde-containing PAE P17 (93% yield, M n = 11.8 kg/mol, Đ = 3.2) using the functionalized aryl dibromide monomer (Figure 2b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…POPs with designed functional groups have emerged as a versatile platform for many potential applications, such as catalysis, sensing, and purification. 1,3,30,31 Our new bottom-up approach allows the installation of functionality using an elaborated monomer. Hence, we prepared aldehyde-containing PAE P17 (93% yield, M n = 11.8 kg/mol, Đ = 3.2) using the functionalized aryl dibromide monomer (Figure 2b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, it was demonstrated that thiophenols can also be used as electrophiles at 160 °C. A modified system was applied to the synthesis of porous poly(aryl thioether)s. 124…”
Section: Cross-couplingsmentioning
confidence: 99%